2013
DOI: 10.1371/journal.pone.0063386
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide Reduces Intracellular Ca2+ Concentration through Suppression of Na+/Ca2+ Exchanger Current in Rat Cardiac Myocytes

Abstract: PurposeAnandamide, one of the endocannabinoids, has been reported to exhibit cardioprotective properties, particularly in its ability to limit the damage produced by ischemia reperfusion injury. However, the mechanisms underlying the effect are not well known. This study is to investigate whether anandamide alter Na+/Ca2+ exchanger and the intracellular free Ca2+ concentration ([Ca2+]i).MethodsNa+/Ca2+ exchanger current (INCX) was recorded and analysed by using whole-cell patch-clamp technique and [Ca2+]i was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…73,74 Recently, in experiments on isolated rat cardiomyocytes, we (Zhang group) have established that anandamide (1-100 nM) dosedependently suppressed the increase in NCX. 75 is one of the triggers of MPTP opening 64 and represents a major source or reperfusion injury in the heart. 73 These results imply that cannabinoid-induced NCX inhibition during ischemia/reperfusion may also contribute to the protection against ischemia/reperfusion.…”
Section: Signaling Pathways Of Cardioprotective Effect Of Exogenous Cmentioning
confidence: 99%
“…73,74 Recently, in experiments on isolated rat cardiomyocytes, we (Zhang group) have established that anandamide (1-100 nM) dosedependently suppressed the increase in NCX. 75 is one of the triggers of MPTP opening 64 and represents a major source or reperfusion injury in the heart. 73 These results imply that cannabinoid-induced NCX inhibition during ischemia/reperfusion may also contribute to the protection against ischemia/reperfusion.…”
Section: Signaling Pathways Of Cardioprotective Effect Of Exogenous Cmentioning
confidence: 99%
“…For example, it has been shown that applying AEA to HEK-293 cells promotes the activation of vanilloid receptors, which, in turn, elevates intracellular calcium ([Ca2ϩ] i ) (112,135). In contrast, AEA has been shown to reduce intracellular calcium concentrations by suppressing Na ϩ /Ca 2ϩ exchanger current in rat cardiac myocytes (74). Interestingly, AEA and 2-AG have also been reported to reduce Ca 2ϩ dependent release of cytochrome c, a mobile electron transport protein, which, when released from mitochondria, can result in mitochondrial swelling and caspase-dependent apoptosis (20,159).…”
Section: Calcium Signaling and Ecs-mediated Regulation Of Mitochondrimentioning
confidence: 99%
“…Cardioprotective mechanisms induced by EC modulation include enhanced Na + /Ca 2+ exchange current 54 , activation of HSP72, PKA, PLC, PKC, eNOS, iNOS, and ERK1/2 55-57 , and regulation of myosin heavy chain isoform switching 50 . Interestingly, α1-AR activation regulates each of these processes in the heart as well, suggesting that the EC system may participate broadly in the mechanisms underlying α1-mediated cardioprotection.…”
Section: Discussionmentioning
confidence: 99%